2018
DOI: 10.3892/ol.2018.9829
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers of lung adenocarcinoma brain metastases via microarray analysis of cDNA expression profiles

Abstract: Brain metastases originating from lung adenocarcinoma (LAD) occur frequently. The aim of the current study was to assess potential biomarkers for the prognosis of lung adenocarcinoma brain metastasis (LAD-BM) through the analysis of gene expression microarrays. The current study downloaded two gene expression datasets, GSE14108 and GSE10245, from the Gene Expression Omnibus database. From GSE14108 and GSE10245, 19 LAD-BM samples and 40 primary LAD samples were selected for analysis. To identify the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…The negative regulation of the cell cycle during G0 and G1 phases was shown in a previous study on OSCC [30]. The chemokine-mediated signaling pathway was earlier found altered in lung cancer [31].…”
Section: Resultsmentioning
confidence: 71%
“…The negative regulation of the cell cycle during G0 and G1 phases was shown in a previous study on OSCC [30]. The chemokine-mediated signaling pathway was earlier found altered in lung cancer [31].…”
Section: Resultsmentioning
confidence: 71%
“…Su et al also reported that cytokine-cytokine receptor interaction was the most significantly enriched signaling pathway in LUAD BM using microarray analysis of cDNA expression profiles (20). Among the genes associated with the cytokine-cytokine receptor interaction identified by Su et al, CCL18 was included in our results (20). The chemokine signaling pathway, an important immunological mediator pathway, was also elevated in BM samples compared to primary LUAD samples (20).…”
Section: Discussionmentioning
confidence: 55%
“…In our study, five genes (CCL18, CCL23, CSF2, IFNAR2, and IL6ST) involved in the cytokine-cytokine receptor interaction pathway were found to be closely related to BM. Su et al also reported that cytokine-cytokine receptor interaction was the most significantly enriched signaling pathway in LUAD BM using microarray analysis of cDNA expression profiles (20). Among the genes associated with the cytokine-cytokine receptor interaction identified by Su et al, CCL18 was included in our results (20).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…To date, only two clinical trials have been conducted on the use of miRNAs in cancer treatment. The results point to the need for further improvements and to the limited knowledge on miRNAs’ mechanisms of action [ 29 ].…”
Section: Discussionmentioning
confidence: 99%